Esophageal achalasia is treated with surgical Heller Cardiomyotomy and Dor Funduplication a rare case report - Frengky, Agus; Putra, Pande Made Gunawan Adi (CV. Publikasi Indonesia, 2025)
Achalasia is an esophageal motility disorder characterized by a lack of peristalsis and impaired relaxation of the lower esophageal sphincter. With elevated LES pressure, the esophageal diameter can increase, and some patients develop end-stage achalasia, such as megaesophagus or sigmoid esophagus with significant dilation and tortuosity. The global annual incidence of achalasia is approximately 1 in 100,000, with an overall prevalence of 9 to 10 per 100,000. Patients most commonly experience dysphagia with liquids, regurgitation, and sometimes chest pain with or without weight loss. Management of this type of achalasia aims to relieve symptoms by improving esophageal emptying and reducing the pressure gradient. This case report discusses a patient who underwent surgical heller cardiomyotomy and dor fundoplication for the management of esophageal achalasia.